Comparison of Aboul-Azm and Fouda’s approach of mixed dentition analysis with Moyers technique - Dikshit, Parajeeta; Limbu, Senchhema; Khanal, Sunita; Malla, Manisha; Dhakal, Lok Raj (Birat Journal of Health Sciences, 2022)
Introduction: The prediction of mesiodistal widths of unerupted canines and premolars are an important aspect of analysis of the developing permanent dentition. Various radiographic as well as non radiographic methods have been tested and researched to predict the width of these teeth. The Moyers mixed dentition analysis is a universally accepted technique. Whereas Aboul-Azm and Fouda’s approach of mixed dentition analysis is a concept that derives the measurement from equation based on the buccolingual width of the permanent first molars. It does not require any table for the prediction.Objective: The present study compares the Aboul-Azm and Fouda’s approach of mixed dentition analysis with Moyers technique.Methodology: Estimations of the widths of the unerupted permanent canines, first and second premolars were performed for maxillary and mandibular arches using Aboul-Azm and Fouda’s and Moyers prediction methods. The predicted values were then compared with the measurements of the actual teeth on 224 study models of males and females. The study was conducted from October to December 2021.Results: The study was conducted on 112 male and female samples each. For males, statistically significant underestimation were found for Aboul-Azm and Fouda’s method in both arches whereas Moyers method showed better accuracy in males. In females Moyers method showed a significant overestimation. In the total sample the Moyers method showed accuracy for maxillary arch whereas Aboul-Azm and Fouda’s method was more accurate for the mandibular arch.Conclusion: Moyers method showed a good accuracy in the maxillary arch while in the mandibular arch Aboul-Azm and Fouda’s method was more accurate.